1993
DOI: 10.1016/s0953-7562(09)81116-7
|View full text |Cite
|
Sign up to set email alerts
|

Cellulolytic enzymes of the obligately biotrophic rust fungus Uromyces viciae-fabae are regulated differentiation-specifically

Abstract: Uredospores of the obUgately biofrophic broad bean rust fungus Uromyces viciae-fabae form infection structures on artificial membranes providing a thigmotropic signal. In nalure these are essential for invasion of the host plant through the stomata. '[his experimental system was used to analyse the production of cellulolytic enzymes duting the differentiation of rust infection stru~lures.Low .cellulase activity was detected in dormant spores and in germ tubes. Enzyme activity increased duting appressorium deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…However, little is known about the regulation of these enzymes in obligately biotrophic fungi. In previous reports (Frittrang e t al., 1992;Heiler et a/., 1993) and in this paper we have demonstrated that the broad bean rust fungus forms cell-wall-degrading enzymes mainly during the time when infection hyphae and haustorial mother cells are differentiated. This differentiation-specific pattern of enzyme formation may explain why cell-wall-degrading enzymes of rust fungi have been overlooked and why their potential role in the infection process has not been recognized .…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…However, little is known about the regulation of these enzymes in obligately biotrophic fungi. In previous reports (Frittrang e t al., 1992;Heiler et a/., 1993) and in this paper we have demonstrated that the broad bean rust fungus forms cell-wall-degrading enzymes mainly during the time when infection hyphae and haustorial mother cells are differentiated. This differentiation-specific pattern of enzyme formation may explain why cell-wall-degrading enzymes of rust fungi have been overlooked and why their potential role in the infection process has not been recognized .…”
Section: Discussionmentioning
confidence: 65%
“…their synthesis requires fungal morphogenesis but not the presence of substrate, and is not subject to catabolite repression. The acidic cellulases start to appear during appressorium development (Heiler et al, 1993), while the formation of PME isoforms B1 and B2 (PIS 5.2 and 5.6) begins with differentiation of young infection hyphae, which are usually enlarged to substomatal vesicles ; Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dikaryotic urediospores of U. viciae-fabae secrete a number of cell-wall-degrading enzymes in a highly regulated manner. Cellulase production occurs already during appressorium formation (Heiler et al 1993), pectinmethylesterases are secreted during infection hypha development, and polygalacturonate lyase is produced during differentiation of haustorial mother cells (Deising et al 1995). Thus, the fungus seems to be adapted to the specific infection conditions found during stomatal penetration and subsequent host cell penetration.…”
Section: Discussionmentioning
confidence: 99%
“…Acidic and neutral cellulase (Heiler et al 1993), extracellular protease (Rauscher et al 1995), chitin deacetylase (Deising and Siegrist 1995), pectin esterase (Frittrang et al 1992), pectin methylesterase (Deising et al 1995a), neutral cellulase (Heiler et al 1993), and polygalacturonate lyase (Deising et al 1995a) activities were found (Fig. 4.5).…”
Section: Biochemical and Molecular Analyses Of Rust Fungimentioning
confidence: 93%